Statistical Assessment of Parameters Affecting Firebrand Pile Heat Transfer to Surfaces - Bearinger, Elias; Lattimer, Brian Y.; Hodges, Jonathan L.; Rippe, Christian; Kapahi, Anil (Frontiers in Mechanical Engineering, 2021)
Firebrands are known to cause ignition of structures far from the primary fire front, resulting in significant damage to structures before firefighting can be attempted. To make structures more resilient to firebrand ignition, a better understanding of the heat transfer from firebrands to surfaces is needed. This paper provides a statistical assessment of different factors expected to have an impact on the heat flux from firebrand piles to a flat surface. The factors included in the study were wood moisture content, wood type (hardwood or softwood), wood density, wood state (live, dead, or artificial), wind speed, pile mass, firebrand diameter, and firebrand length. Using design of experiments, test matrices were developed that permitted a statistical analysis to be performed on the data. This statistical analysis was used to quantify which factors had a statistically significant impact on the heat flux from the pile as well as ranking the importance of the different factors. Artificial firebrands were found to have statistically higher heat fluxes compared with natural firebrands. Other factors that had a statistically significant impact on the heat flux were wind speed, firebrand length, and firebrand length-diameter interaction. Firebrand aspect ratio (related to the firebrand length-diameter interaction) is directly related to the pile porosity, which is a measure of the volume of air in the pile. Increasing the aspect ratio (which increases the pile porosity) results in higher heat fluxes across a larger region of the pile and was found to be an important factor. Firebrand diameter and pile mass were found to affect the burning duration but not as significantly as other parameters. The number of firebrands in the pile was also observed to potentially affect the heat flux, with a critical number required to reach the highest heat flux for a given firebrand geometry.